Daytime and nighttime aerosol soluble iron formation in clean and slightly polluted moist air in a coastal city in eastern China - W. Li; W. Li; Y. Qi; Y. Qi; Y. Liu; Y. Liu; G. Wu; G. Wu; Y. Zhang; Y. Zhang; J. Shi; W. Qu; et al. (Atmospheric Chemistry and Physics, 2024)
Photocatalytic reactions during the daytime, alongside aqueous-phase reactions occurring during both daytime and nighttime, are identified as the two primary processes facilitating the conversion of aerosol iron (Fe) from the insoluble state to the soluble state within the atmospheric environment. This study investigated the levels of total Fe (FeT) and soluble Fe (FeS) in PM2.5 samples collected during daytime and nighttime in Qingdao, a coastal city in eastern China, evaluating the distinctive roles of these two pathways in enhancing aerosol Fe solubility (%FeS, defined as the ratio of FeS to FeT). Under clean and humid conditions, characterized by prevailing sea breezes and a relative humidity (RH) typically above 80 %, an average daytime %FeS of 8.7 % was observed, which systematically exceeded the nighttime %FeS (6.3 %). Photochemical conversions involving oxalate contributed to the higher %FeS observed during daytime. Conversely, in scenarios where air masses originated from inland areas and exhibited slightly polluted, daytime %FeS (3.7 %) was noted to be lower than the nighttime %FeS (5.8 %). This discrepancy was attributable to the variations in RH, with nighttime RH averaging around 77 %, conducive to the more efficient generation of acidic compounds, thereby accelerating FeS production compared to the daytime, when RH was only about 62 %. Furthermore, the oxidation rates of sulfur (SOR) displayed a strong correlation with RH, particularly when RH fell below 75 %. A 10 % increase in RH corresponded to a 7.6 % rise in SOR, which served as the primary driver of the higher aerosol acidity and %FeS at night. These findings highlight the RH-dependent activation of aqueous-phase reactions and the augmentation of daytime photocatalysis in the formation of FeS in the coastal moist atmosphere.